PENGARUH SHOPPING LIFESTYLE DAN DISCOUNT TERHADAP IMPULSE BUYING DI TANGGAL CANTIK PADA TOKOPEDIA - Dalaya Rasuly; Nurul Hidayatin Nisa (CV. ADIBA AISHA AMIRA, 2024)
The development of technology and information in Indonesia has grown rapidly, causing changes in shopping patterns. This is marked by the emergence of e-commerce as a means of online sales transactions. One of them is Tokopedia, which is the e-commerce most visited by Indonesian people. This research aims to analyze the influence of Shopping Lifestyle and Discounts on Impulse Buying on beautiful dates on Tokopedia. This research is quantitative research with the variables Shopping Lifestyle (X1), Discount (X2) and Impulse Buying (Y). The data collection technique used a questionnaire distributed to 100 respondents, namely students from three state universities in Malang City. Respondents were selected using purposive sampling technique. Data analysis using questionnaire testing, descriptive analysis, classical assumption testing, multiple regression analysis, determinant analysis and hypothesis testing. The results of partial hypothesis testing show that lifestyle shopping and discounts have a positive influence on impulse buying. Simultaneous test results show that lifestyle shopping and discounts have a positive influence on impulse buying. Based on the results of this research, it is hoped that Tokopedia will maximize the discount program provided and sell quality products so that consumers make unplanned purchases on Tokopedia